Prevalence of human papillomavirus infection of 65,613 women in East China - Yanmei Ge; Shanliang Zhong; Meng Ren; Yanping Ge; Yuan Mao; Peng Cao (BMC, 2019)
Abstract Background The infection with human papillomavirus (HPV) is the major cause of genital disease. This study assessed the prevalence and genotype of HPV among outpatient women and healthy women in Jiangsu, East China. Methods A total of 65,613 women aged 16-85 years were recruited from Nanjing Kingmed Diagnostics, including 45,736 outpatients and 19,877 healthy women. The cervico-vaginal cells were collected and then HPV types were detected using the Tellgenplex™ HPV DNA Test. Results The overall HPV prevalence was 17.7% for outpatients and 10.6% for healthy women. 13.7% outpatients were infected with a single HPV type and 4.0% were infected with multiple HPV types. Regarding healthy women, 8.5 and 2.1% were infected with single and multiple HPV types, respectively. The two most commonly detected HPV types were HPV 16 and 58 regardless of single- or multiple-type infection or source of the participants. HPV16 + 58 was the most commonly identified multiple genotype in outpatients, while HPV16 + 52 was frequently detected in healthy women. Highest prevalence rate was found in outpatients aged < 20 years and ≥ 60 years. Conclusions This study revealed the prevalence characteristics of HPV in both outpatient women and healthy women in Jiangsu province.